PARADOKS “KNOWLEDGE IS POWER” DAN BENCANA KEMANUSIAAN Tinjuan Filosofis Menurut Pemikiran Sir Francis Bacon - Sirus Yulius Mbusa (Aggiornamento, 2021)
Disaster is an actual phenomenon. There are many disasters that hit human life. Disasters are often understood as natural disasters, but the disasters that will be discussed in this paper are disasters of misuse of knowledge. Humans have intelligence so humans have knowledge. Human knowledge aims to make humans more and more human. But in reality man experiences suffering for his own knowledge. Mistakes in using knowledge greatly affect human life and become a humanitarian disaster. Thus the thought of Sir Francis Bacon directs humans to use knowledge as it should. Knowledge is used to advance human life. To clarify the discussion in this article, the author uses a literature study by presenting several themes, namely the background of Sir Francis Bacon's thoughts, getting to know more about humanitarian disasters and the relationship between "knowledge is power" and humanitarian disasters. The relevance of this paper is to criticize the misuse of knowledge in society because it will be a disaster for humans themselves.